False-positive results for seasonal coronavirus infections on using the FilmArray Pneumonia Panel - Kuenyoul Park; Bosung Park; Eun Jeong Won; Heungsup Sung; Mi-Na Kim (Microbiology Spectrum)
ABSTRACT The FilmArray Pneumonia Panel (FilmArrayPN; bioMérieux) was tagged for potential false-positive seasonal coronavirus results, possibly caused by non-specific amplification or cross-reactivity with human genomic DNA. This study was conducted to determine the real-world false-positive rate of seasonal coronavirus infections using FilmArrayPN at a tertiary care hospital. We retrospectively reviewed FilmArrayPN results to detect lower respiratory tract pathogens from July 2023 to April 2024. Allplex Respiratory Panel (AllplexRP; Seegene) and/or FilmArray Respiratory Panel (FilmArrayRP) results for the same patient were considered as reference results. In the last month of the study period, all positive samples in FilmArrayPN were confirmed by AllplexRP and pan-coronavirus targeted PCR (pan-CoV PCR). A total of 2,120 specimens, including 1,847 expectorated sputum and 273 bronchial aspirate (BA) samples, were tested by FilmArrayPN. Of these, 161 (8.7%) sputum and 7 (2.6%) BA specimens from 152 patients were positive for coronavirus targets in FilmArrayPN. Of the 122 cases also tested by AllplexRP and/or FilmArrayRP, 106 specimens (86.9%) were coronavirus-negative, except for 9 OC43-positive, 6 229E-positive, and 1 NL63-positive. Notably, 83.1% of the 106 cases that tested negative in the other tests had melting temperatures above 83℃. A total of 61 specimens that tested positive for coronavirus in FilmArrayPN but negative in AllplexRP were confirmed to be negative in pan-CoV PCR. The coronavirus positivity of 7.8% in the FilmArrayPN resulted in 5% of samples being potentially misreported as false-positives. This report thus highlights the need for continuous monitoring of melting temperatures to avoid potential false-positives.IMPORTANCEThe FilmArray Pneumonia Panel (FilmArrayPN; bioMérieux) was tagged for potential false-positive seasonal coronavirus results, possibly caused by non-specific amplification or cross-reactivity with human genomic DNA. FilmArrayPN results were retrospectively reviewed from July 2023 to May 2024. Of 2,120 tested specimens, 168 specimens from 152 patients were positive for coronavirus targets in FilmArrayPN. Of the 122 cases also tested by Allplex Respiratory Panel and/or FilmArray Respiratory Panel, 106 specimens (86.9%) were coronavirus-negative. Notably, 83.1% of the 106 cases that tested negative in the other tests had melting temperatures above 83℃. A total of 61 specimens that tested positive for coronavirus in FilmArrayPN but negative in Allplex were confirmed to be negative in pan-coronavirus targeted PCR. The coronavirus positivity of 7.8% in the FilmArrayPN resulted in 5% of samples being potentially misreported as false-positives. This report highlights the need for continuous monitoring of melting temperatures to avoid potential false-positives.